PENGARUH LATIHAN GERAK STRETCHING KAKI TERHADAP PENURUNAN TINGKAT NYERI EKSTRIMITAS BAWAH PADA LANSIA DENGAN OSTEOATRITIS DI RW 04 KELURAHAN JURANG MANGU BARAT TAHUN 2017 - Ega Salamah; Lisna Agustina (STIKes IMC Bintaro, 2017)
Osteoarthritis is a disease that many occur in elderly that majority caused existence of physiological changes in musculosceletal and cause pain complaints on the joint and the most frequently attacking the lower extremity joint, it can interfere with comfort and daily activities. Non pharmacological therapy is one of prevention and complementary therapies to reduce lower extremity pain levels in osteoarthritis. This study aims to determine the effect of stretching to decrease the scale of lower extremity pain. this study is use quasy experimental designwith pretest posttest with non equivalent control group design. Sampling technique is done by way purpossive sampling obtained 50 respondents that divided into groups of intervention and control groups. The results of t-test analysis show there are differences in pain scale pre-post test in intervention group (p=0,000/p<0,05), however there is no difference in control group (p=0,327/0>0,05). Recommended for health care providers and respondents to using non pharmacological therapy (stretching) as Prevention and treatment of medical drug companion.